Controle social e judicial do orçamento público: uma abordagem sob a perspectiva da cidadania participativa - Marques, Antonio Sérgio Peixoto (2008)
This study has the purpose of demonstrating that the public budget is a basic instrument for the accomplishment of public politics that take care of to the minimum of existence of the citizen, since it is submitted to a new reading under the approach of the Constitutional State and is under the effective control of the citizenship and the Judiciary Power. Objectifying the understanding of the problem, the factors that had unchained a deep disequilibrium between the public resources and to the pressing necessities of the citizen, fruit of inefficient decisions in moving to the public expenses and the absence of priorities in the application of the public resources had been presented. This fact opens space for a new boarding of the citizenship: the participation of citizenship. The full exercise of this citizenship will allow a continuous dialogue with the Public Power, from an effective social control on the public budget, as well as of the search of the judicial guardianship with I look to guarantee it the full exercise of this participates to citizen in the elaboration process and budgetary execution. The relation of the economy was evidenced and of the right in moving to the public budget and how the citizenship can intervine with the objective to guarantee the efficiency of the public expense in order to take care of to the basic necessities of the citizens. Finally, the judicial control of the public budget is presented as guarantee of the exercise of the social control and vice versa, occasion where the beddings and limits of these controls had been delineated, which is guided by the basic rights, more necessarily, the essential nucleus of these rights.